The Concept of School Literacy Movement Through Reading Time at SDIT Raudaturrahmah Pekanbaru - Erwinsah Erwinsah; Mutsyuhito Solin; Abdurrahman Adisaputera (BIRCU, 2019)
Reading time is a practice carried out by the school to support the literacy movement in Pekanbaru's Raudaturrahmah SDIT school, the program is held on Friday after Friday prayers, students are provided with 30 minutes of reading any books in school, and students bring books from home, and each week students have to report to the class teacher the results of the books they read, and at the end of each semester the class teacher reports to the school head as a result of reading time. The aim of this research is to analyze GLS activity and program in SDIT Raudaturrahmah Pekanbaru. This research used a qualitative descriptive study, namely research that intends to understand the phenomenon experienced by research subjects holistically by describing it in the form of words in a specific natural context and by utilizing various natural methods as well. The result is The GLS concept applied by SDIT Raudaturrahmah Pekanbaru is at the stage of developing GLS, and has a special GLS program that is reading time which is held every Friday with a time allocation of 30 minutes.